An Analogy Based System to Track Material Management on Site: Optimizing Material Management in Urban Construction Sites (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The most commonly used method for space management in the construction industry is the development of site plans. While these plans outline how to manage material deliveries, staging areas and crane locations for construction job sites in suburban areas, they are inadequate for those in congested, urban areas. This study focuses on the floor-level construction material layout which is required for multiple-floor building where multiple construction works occur simultaneously in close proximity. By minimizing excessive re-positioning of construction materials, the floor-level construction material layout would assist in finding sufficient space for construction materials in urban areas where space is limited around the building sites.